2012
DOI: 10.1103/physrevb.85.033404
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe microscopy imaging of metallic nanocontacts

Abstract: We show scanning probe microscopy measurements of metallic nanocontacts between controlled electromigration cycles. The nanowires used for the thinning process are fabricated by shadow evaporation. The highest resolution obtained using scanning force microscopy is about 3 nm. During the first few electromigration cycles the overall slit structure of the nanocontact is formed. The slit first passes along grain boundaries and then at a later stage vertically splits grains in the course of consuming them. We find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 24 publications
(34 reference statements)
11
36
3
Order By: Relevance
“…The increase in the asymmetry of the temperature fields can be qualitatively understood by hypothesizing that voids/vacancies are created and accumulated primarily in the cathode of the device (see SI). This hypothesis is consistent with previous studies that have observed the accumulation of voids in nanoscale devices910131430.…”
Section: Resultssupporting
confidence: 93%
“…The increase in the asymmetry of the temperature fields can be qualitatively understood by hypothesizing that voids/vacancies are created and accumulated primarily in the cathode of the device (see SI). This hypothesis is consistent with previous studies that have observed the accumulation of voids in nanoscale devices910131430.…”
Section: Resultssupporting
confidence: 93%
“…For electron microscopy (i.e., SEM, TEM, or related techniques), planar, free-standing nanocontacts or nanocontacts supported by an electron-transparent substrate are needed (Kondo and Takayanagi, 1997). For scanning probe techniques, two different geometries have been used: planar nanocontacts on insulating substrates have been imaged by scanning force microscopy (SFM) (St€ offler et al, 2012;Girod et al, 2012;Durkan and Welland, 2000a;and Durkan et al, 1999), or the tip of a scanning tunneling or force microscope has been brought into contact with a metallic surface (Gimzewski and M€ oller, 1987;Limot et al, 2005;Ternes et al, 2011;Oliver et al, 2012;and Hansen et al, 2000). The metallic contacts are required to be atomically flat.…”
Section: A General Overviewmentioning
confidence: 99%
“…The microcrystalline properties of the metal films strongly depend on the substrate, precise deposition method and parameters, and the film thickness. In experiments on Si 3þx N 4Àx , the Au grains have sizes between 10 and 100 nm (Strachan et al, 2006(Strachan et al, , 2008and Heersche et al, 2007), similar to oxidized bulk Si, where the typical grain size is about 30 nm (St€ offler et al, 2012). The contacts are usually produced by electron-beam lithography in a bow-tie or similar structure with a weak point at which breakage is expected.…”
Section: Grain Boundary Electromigrationmentioning
confidence: 99%
“…Additionally, we have performed STM and highresolution scanning force microscopy measurements on similar samples prepared by evaporation through stencil masks 13 . These measurements show no indication of the presence of molecules on the surface.…”
Section: Resultsmentioning
confidence: 99%